Clinical adverse events related to the use of femoral and radial artery access in patients who underwent interventional cardiology procedures in the Hospital Nacional Hipólito Unanue - Sapo Solano , Lisset Haydee (2022)
Objective: To determine the clinical adverse events related to the use of femoral and radial artery access in patients who underwent interventional cardiology procedures in the Hospital Nacional Hipólito Unanue from 2015 to 2017. Materials and methods: A comparative, retrospective, observational and analytical study was conducted with a total of 151 medical records of patients who had clinical adverse events. Medical record review was used as data collection technique, and a data collection sheet designed by the researcher was used as instrument. The R software was used for the analysis. Results: Out of 151 cardiac catheterizations, 51.66 % were performed by a femoral artery access and 48.34 % by a radial artery access. The average age of the patients was 59.6 ± 11.3 years, out of which 39.73 % ranged between 60 and 70 years, and 73.50 % of the patients were males. The most frequent comorbidities were arterial hypertension and diabetes mellitus. Non-serious clinical adverse events occurred as a result of both vascular access procedures; however, their incidence was high. Fifty percent (50%) of the patients who underwent a femoral artery access procedure showed the following adverse events: hematoma (25.60 %), bleeding (9 %), ischemia (1.30 %), vagal response (1.30 %), pseudoaneurysm (1.30 %), a rare skin rash that looked like a burn (1.30 %) and pain (10.20 %). In contrast, 19.14 % of the patients who underwent a radial artery access procedure presented hematoma (8.21 %), bleeding (2.73 %), radial artery spasm (1.40 %) and pain (6.80 %). Conclusions: After determining the clinical adverse events, it was concluded that radial artery access is better than femoral artery access for interventional cardiology procedures.